Investment determinants of fitness SMEs in Portugal - Nunes, Paulo Maçãs; Serrasqueiro, Zélia; Guedes de Carvalho, Pedro (Technological and Economic Development of Economy, 2014)
Based on a sample of 182 Portuguese fitness SMEs we study the investment determinants of fitness SMEs in Portugal. The multiple empirical evidence obtained in this study lets us conclude that the main explanatory theories of firm investment cannot be considered mutually exclusive in explaining the investment of Portuguese fitness SMEs, since: 1) they adjust investment as a function of sales, corroborating the assumptions of Neoclassical theory; 2) cash flow is an important financial resource for investment, corroborating the assumptions of Free Cash Flow theory; and 3) external finance, namely debt, is a restrictive determinant of investment, which corroborates the assumptions of Agency theory. Besides these results, we find that growth opportunities and government subsidies are positive determinants of investment in Portuguese fitness SMEs, and the financial crisis of 2008 has a negative influence on investment in Portuguese fitness SMEs. The financial crisis of 2008 also means greater relative importance of cash flow and government subsidies for increased investment, and debt for diminished investment, in fitness SMEs.